2012
DOI: 10.1159/000338251
|View full text |Cite
|
Sign up to set email alerts
|

Laser Interstitial Thermal Therapy for Focal Cerebral Radiation Necrosis: A Case Report and Literature Review

Abstract: Whole-brain radiotherapy and stereotactic radiosurgery (SRS) play a central role in the treatment of metastatic brain tumors. Radiation necrosis occurs in 5% of patients and can be very difficult to treat. The available treatment options for radiation necrosis include prolonged high-dose corticosteroids, hyperbaric oxygen, anticoagulation, bevacizumab, and surgical resection. We present the first report and results using laser-interstitial thermal therapy (LITT) for medically refractory radionecrosis. A 74-yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
89
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(96 citation statements)
references
References 103 publications
4
89
1
2
Order By: Relevance
“…In a small series of patients with histologically-proven radiation necrosis treated with LITT [15], Torres-Reveron et al [15] described all patients as tolerating the procedure well enough to be discharged within 48 hours; four had durable improvement of neurological symptoms, and all were weaned off steroids within two months. Other authors have published similar results [24,37,38].…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…In a small series of patients with histologically-proven radiation necrosis treated with LITT [15], Torres-Reveron et al [15] described all patients as tolerating the procedure well enough to be discharged within 48 hours; four had durable improvement of neurological symptoms, and all were weaned off steroids within two months. Other authors have published similar results [24,37,38].…”
Section: Discussionsupporting
confidence: 67%
“…In a small series of patients with histologically-proven radiation necrosis treated with LITT [15], Torres-Reveron et al [15] described all patients as tolerating the procedure well enough to be discharged within 48 hours; four had durable improvement of neurological symptoms, and all were weaned off steroids within two months. Other authors have published similar results [24,37,38].Importantly, we and others have concluded that short-term follow-up MRI must be interpreted carefully when assessing treatment effect. For two weeks to two months following LITT, lesions tend to increase in size, but develop a thinner "eggshell" rim of enhancement.…”
supporting
confidence: 76%
See 1 more Smart Citation
“…13,14 Radiation therapy has been an integral part of treating certain cancers like highgrade gliomas, and a risk was the development of radiation necrosis. 18 Potential therapies include medicine (e.g., high doses of cortical steroids or monoclonal antibodies 16 ) and resection; for patients who are not strong candidates for surgery and who have medically refractory radiation necrosis, LITT is potentially an alternative.…”
Section: Fig 1 A: Preoperative Axial Mr Image Showing Infratentoriamentioning
confidence: 99%
“…18 Potential therapies include medicine (e.g., high doses of cortical steroids or monoclonal antibodies 16 ) and resection; for patients who are not strong candidates for surgery and who have medically refractory radiation necrosis, LITT is potentially an alternative. 7,13 For instance, Torres-Reveron et al used LITT to successfully treat two cases of cerebellar lesions in which one patient tested positive for tumor recurrence and the other for radiation necrosis. 19 Our report provides further evidence that LITT is a viable treatment option when more conventional therapies are contraindicated.…”
Section: Fig 1 A: Preoperative Axial Mr Image Showing Infratentoriamentioning
confidence: 99%